"Stem-cell therapy" is the last option for cardiac disease? - Rahman, MM; Siddiqui, MMR; Haque, KMHS S; Ahmed, MK; Parvin, T; Subedi, B (University Heart Journal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> As cardiovascular disease is the leading cause of death worldwide. Among them Ischaemic heart disease is the primary cause of mortality and morbidity throughout the world, including most low income and middle income countries. Obstruction of coronary arteries leads to myocardial infarction with associated death of cardiomyocytes. This overloads the surviving myocardium and eventually leads to heart failure. Previously there have existed very few and very limited therapeutic options for either of these conditions. In the past, there has not been any treatment for reversing cardiac scar tissue, nor for regenerating the cardiac tissue that is damaged from a heart attack and therapies only help to delay the progression of the disease process. Laboratory experiments and recent clinical trials suggest that cell - based therapies can improve cardiac function and the implications of this for cardiac regeneration are causing great excitement. New discoveries on the regenerative potential of stem cells and progenitor cells for treating and preventing heart failure have transformed experimental research and led to an explosion in clinical investigation. In this review, we discuss the current knowledge of regeneration in the adult mammalian heart. We also consider the various stem-cell and progenitor-cell types that might regenerate the myocardium and review the major challenges to such therapy. Â  University Heart Journal Vol.4(1) January 2008